INSTITUTIONAL DESIGN OF ANALYTICAL TOOLS OF THE FINANCIAL CONTROL INSTITUTION - Andrii Khmelkov (Соціальна економіка)
The article is devoted to the search for ways to achieve the stability of public finances, through the modernization of relations that positively change the infrastructure of the financial environment and, first of all, it concerns the institutions operating in it. The object of the research is the Institute of Financial Control. The subject of the study is analytical tools of diagnosis and assessment of the quality of state financial control in the country by agents of the Institute of Financial Control. The use of analytical tools with the specified purpose can be attributed to work with large data, i.e. "big data", and the process of using them as work with "raw data" with the help of "data mining" and "data extraction".